Acute effects of jaw clenching while wearing a customized bite-aligning mouthguard on muscle activity and force production during maximal upper body isometric strength - Adrià Miró; Bernat Buscà; Jordi Arboix-Alió; Pol Huertas; Joan Aguilera-Castells (Elsevier, 2023)
Background/Objective: The possible mechanisms supporting the relationship between the masticatory and the musculoskeletal systems have been recently investigated. It has been suggested that jaw clenching promotes ergogenic effects on prime movers through the phenomenon of concurrent activation potentiation (CAP). The purpose of this study was to analyse the effects of jaw clenching and jaw clenching while wearing mouthguard (MG) on muscle activity and force output during three upper body isometric strength tests. Methods: Twelve highly trained rink-hockey athletes were recruited for the study. A randomized, repeated measures within study design was carried out to compare the acute effects of three experimental conditions: jaw clenching while wearing MG (MG), jaw clenching without MG (JAW) and non-jaw clenching (NON-JAW). Results: Statistical analyses revealed significant higher force output (p < 0.05) in all tests for MG conditions with respect to NON-JAW. When comparing JAW and NON-JAW conditions an increased peak force was found in handgrip (p = 0.045, d = 0.26) and bench press (p = 0.018, d = 0.43) but not in biceps curl (p = 0.562, d = 0.13). When comparing MG and JAW conditions, no differences were observed in any force output. In terms of muscle activity, significant differences were found in the agonist muscles of the handgrip test for MG with respect to NON-JAW (p = 0.031-0.046, d = 0.25-1.1). Conclusion: This study demonstrated that jaw clenching, with and without MG, may be a good strategy to elicit the CAP phenomenon, which seems to promote ergogenic effects in upper body isometric force production. The non-significant differences observed between JAW and MG suggested that the use of MG doesn't make a difference in enhancing the isometric force production neither the muscle activity in upper body isometric strength.